FIELD APPLICATION OF EXPANDING RIGID POLYURETHANE STABILIZATION OF RAILWAY TRACK SUBSTRUCTURE - Warren, Benjamin (My University, 2015)
Executive Summary This project includes the use of expanding rigid polyurethane foam to remediate substructure deficiencies in railroad track at a field site in Illinois. Soft substructure soils exhibit creep or consolidation that lead to excess track settlement. Cyclic loading from passing trains can fail the subgrade, with progressive cyclic shear failure. Track settlement and progressive shear failure were found at a field sites in Dayton, Illinois. Following a geotechnical and geophysical investigation of the sites, URETEK USA planned a polyurethane injection strategy to compress the subgrade soils and permeate the subballast layer. Polyurethane injection was compared to traditional railroad maintenance with a Life-Cycle Cost Analysis and Life-Cycle Analysis. Due to weather and scheduling difficulties, the injection results will be appended and included in a final, updated report. A full-scale prototype model is often the ideal simulation of the final product for field application. Therefore, in geotechnical engineering, different models are developed to test proposed construction methods, interaction between elements, and field performance. Areas where experimental products are used in full-scale applications, and that are constructed with traditional equipment and techniques, are invaluable to researchers and industry alike. The prototyped product can be evaluated in real-world conditions, where not all variables can be closely controlled. Laboratory tests, while important, cannot replicate porewater distributions and soil heterogeneity in the environment where the product is proposed for use. The expanding rigid polyurethane enhanced ballast research began in 2011 with Keene (2012) investigating the performance of clean ballast injected with polyurethane (PUR) in a collaboration of with UW-Madison and URETEK USA. PUR strengthened the ballast layer in both compression and flexural tests. Dolcek (2013) investigated the same PUR, but with injection into ballast with varying amounts of fouling (fine) materials and water content. Similar to Keene (2012), the mechanical behavior was enhanced in both compression and flexural, but flexural performance of fouled ballast was below that of the clean ballast. Enhancement of the ballast layer was proven over repeated experiments with different ballast types and gradations and resulted in the motivation to test this technology in the field. A railroad track site was chosen in Dayton, Illinois, for which fraccing sand is transported to test the performance of a substructure deficient section of railroad injected with PUR. This spur line receives fully loaded unit trains on a near daily basis. Car switching and train assembly (putting cars in proper positions for transportation) occurs here as well. The track borders the Fox River, and there are substructure problems with: soft soil, settlement, and embankment failures along this stretch of track. To clarify what the contributing underlying problems are at the track field site, the ?Dayton Dip,? geotechnical and geophysical investigations were conducted. URETEK USA/ICR provided Dynamic Cone Penetrometer logs, which give an indication of soil strength. The UW-Madison team conducted Ground Penetrating Radar, Electrical Resistivity Tomography, Time Domain Reflectometry, and excavated test pits to take samples to run engineering property tests in a laboratory setting. The data from these different tests collectively verified the hypothesis of a highly fouled ballast layer, with a soft saturated clay subgrade beneath. There were classic subgrade shear failures along the track and at bridge approaches; i.e., the ?bump at the end of the bridge? in which an abrupt change in track stiffness causes differential settlement. The investigation assisted in the design of two types of polyurethane injection: one to strengthen the subballast and one to strengthen and stiffen soft subsurface material. With URETEK USA?s background in polyurethane injection for infrastructure projects, including rail crossings, their expertise was necessary in designing a functional and economical injection package. The injection was proposed as a combination of subballast layer strengthening and URETEK Deep Injection (UDI) to strengthen and stiffen the subgrade. Due to imposed restrictions of the railroad, PUR could not be placed within 30 cm of the bottom of the tie. The evaluation of polyurethane injection included mobilization and construction costs, track stiffening, maintenance, and environmental impact. Fast construction time decreases user costs and inconveniences. Furthermore, environmental impact has become an important consideration in construction projects. Polyurethane injection can fulfill these metrics. A life-cycle cost analysis was conducted with inputs from URETEK and Wisconsin and Southern Railroad, over a ten-year period. Over a 10-year period, PUR injection appears to be a superior improvement methodology to traditional maintenance resulting in a cost savings from $1000 - $20,000 depending on discount rate. In the life-cycle analysis, PUR injection results in use of water, and CO2 emissions, 82%, and 5% respectively, compared to traditional maintenance methods. After the ongoing portion of this project are completed, various instruments and techniques will be used to monitor the rail section. To measure the dynamic properties and track modulus, strain gauges will be used to measure the cumulative strain in the super-structure and sub-structure of the track. Survey reflectors will be installed every 2 m on both sides of the rail to measure settlement and differential settlement between rails. Finally, settlement rods will be installed to isolate the response of different layers and their corresponding contribution to the permanent deformation in the railroad track. An un-injected control section will be also instrumented to compare results and assess PUR effectiveness. Due to schedule constraints (e.g., early onset of cold weather in 2014), the injections were not completed before the completion of this thesis. Therefore, when the pilot study is completed and analyzed, results will be appended, and a final, updated report issued to the project sponsors. Included in the Appendix are laboratory tests of environmental impacts on polyurethane stabilized fouled ballast and rigid polyurethane foam. Freeze-thaw cycling was conducted; degradation was tracked and tested with non-destructive methods and cyclic triaxial testing. No effect was determined after 20-freeze-thaw cycles. Long term water absorbance of polyurethane foam was investigated. Samples were submerged for 120-days then tested in unconfined compression. Minimal, approximately 3%, changes were seen from ideal polyurethane samples. The results from freeze-thaw cycling and water absorbance indicate that PUR will remain stable in field conditions.